Transcriptomic signatures related to the obesity paradox in patients with clear cell renal cell carcinoma: a cohort study. Issue 2 (February 2020) - Sanchez, Alejandro; Furberg, Helena; Kuo, Fengshen; Vuong, Lynda; Ged, Yasser; Patil, Sujata; Ostrovnaya, Irina; Petruzella, Stacey; Reising, Albert; Patel, Parul; Mano, Roy; Coleman, Jonathan; et al.
Summary: Background: Obesity is associated with an increased risk of developing clear cell renal cell carcinoma (RCC) but, paradoxically, obesity is also associated with improved oncological outcomes in this cancer. Because the biological mechanisms underlying this paradoxical association are poorly understood, we aimed to identify transcriptomic differences in primary tumour and peritumoral adipose tissue between obese patients and those at a normal weight. Methods: In this cohort study, we assessed data from five independent clinical cohorts of patients with clear cell RCC aged 18 years and older. Overweight patients were excluded from each cohort for our analysis. We assessed patients from the COMPARZ phase 3 clinical trial, a cohort from the Cancer Genome Atlas (TCGA), and a Memorial Sloan Kettering (MSK) observational immunotherapy cohort for their inclusion into our study. We assessed overall survival in obese patients (those with a body-mass index [BMI] ≥30 kg/m 2 ) and in patients with a normal weight (BMI 18·5–24·9 kg/m 2, as per WHO's BMI categories), defined as the time from treatment initiation (in the COMPARZ and MSK immunotherapy cohorts) or surgery (in the TCGA cohort) to the date of any-cause death or of censoring on the day of the last follow-up. We also evaluated and validated transcriptomic differences in the primary tumours of obese patients compared with those of a normal weight. We compared gene-expression differences in peritumoral adipose tissue and tumour tissue in an additional, prospectively collected cohort of patients with non-metastatic clear cell RCC (the MSK peritumoral adipose tissue cohort). We analysed differences in gene expression between obese patients and those at a normal weight in the COMPARZ, TCGA, and peritumoral adipose tissue cohorts. We also assessed the tumour immune microenvironment in a prospective cohort of patients who had nephrectomy for localised RCC at MSK. Findings: Of the 453 patients in the COMPARZ trial, 375 (83%) patients had available microarray data, pretreatment BMI measurements, and overall survival data for analyses, and we excluded 119 (26%) overweight patients, leaving a final cohort of 256 (68%) patients from this study for our analyses. From 332 patients in the TCGA cohort, we evaluated clinical and demographic data from 152 (46%) patients with advanced (ie, stages III and IV) clear cell RCC treated by nephrectomy; after exclusion of 59 (39%) overweight patients, our final cohort consisted of 93 (61%) patients. After exclusion of 74 (36%) overweight patients from the initial MSK immunotherapy study population of 203 participants, our final cohort for overall survival analysis comprised 129 (64%) participants. We found that overall survival was longer in obese patients than in those with normal weight in the TCGA cohort, after adjustment for stage or grade (adjusted HR 0·41, 95% CI 0·22–0·75), and in the COMPARZ clinical trial after adjustment for International Metastatic RCC Database (IMDC) risk score (0·68, 0·48–0·96). In the MSK immunotherapy cohort, the inverse association of BMI with mortality (HR 0·54, 95% CI 0·31–0·95) was not significant after adjustment for IMDC risk score (adjusted HR 0·72, 95% CI 0·40–1·30). Tumours of obese patients showed higher angiogenic scores on gene-set enrichment analysis-derived hallmark gene set angiogenesis signatures than did those of patients at a normal weight, but the degree of immune cell infiltration did not differ by BMI. We found increased peritumoral adipose tissue inflammation in obese patients relative to those at a normal weight, especially in peritumoral fat near the tumour. Interpretation: We found aspects of the tumour microenvironment that vary by BMI in the tumour and peritumoral adipose tissue, which might contribute to the apparent survival advantage in obese patients with clear cell RCC compared with patients at a normal weight. The complex interplay between the clear cell RCC tumour and peritumoral adipose tissue microenvironment might have clinical relevance and warrants further investigation. Funding: Ruth L Kirschstein Research Service Award, American Society of Clinical Oncology Young Investigator Award, MSK's Ludwig Center, Weiss Family Kidney Research Fund, Novartis, The Sidney Kimmel Center for Prostate and Urologic Cancers, and the National Institutes of Health (National Cancer Institute) Cancer Center Support Grant.